2016
DOI: 10.1080/17439884.2016.1182924
|View full text |Cite
|
Sign up to set email alerts
|

Composing across modes: a comparative analysis of adolescents’ multimodal composing processes

Abstract: Although the shift from page to screen has dramatically redefined conceptions of writing, very little is known about how youth compose with multiple modes in digital environments. Integrating multimodality and multiliteracies theoretical frameworks, this comparative case study examined how urban twelfth-grade students collaboratively composed across three multimodal projects when responding to and analyzing literature. Data sources included screen capture and video observations, student design interviews, writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 44 publications
2
57
0
1
Order By: Relevance
“…This research demonstrates how students work together on a wide range of multimodal projects (e.g. digital videos, podcasts, webpages) and at all stages of the composing process – including brainstorming ideas, composing with digital tools, editing and presenting final products (Bruce, ; Smith, ). Research also illustrates how the multifaceted nature of multimodal projects allows for the distribution of tasks.…”
Section: Research On Collaborative Multimodal Composingmentioning
confidence: 87%
“…This research demonstrates how students work together on a wide range of multimodal projects (e.g. digital videos, podcasts, webpages) and at all stages of the composing process – including brainstorming ideas, composing with digital tools, editing and presenting final products (Bruce, ; Smith, ). Research also illustrates how the multifaceted nature of multimodal projects allows for the distribution of tasks.…”
Section: Research On Collaborative Multimodal Composingmentioning
confidence: 87%
“…DST allows students to leverage the availability of online resources and reflect on their own learning (Yang, ). Pairing their writing with multiple semiotic modes is particularly empowering for learners with limited language capacity, as multimodality can create additional layers of meaning and complete the message (Smith, ).…”
Section: What Is Dst?mentioning
confidence: 99%
“…Many modern students scour YouTube videos to teach themselves, and some even produce their own videos or run their own YouTube channels. With more students exploring new forms of media, schools are looking for effective ways to leverage digital media to enhance student learning (Smith, ). The practice of digital storytelling (DST) has attracted much attention in education because of the effective ways in which it motivates and engages students, amplifies their voices and networks, and simultaneously develops both traditional literacies of reading and writing and new literacies of digital production and communication (Cummins, Hu, Markus, & Montero, ; Smeda, Dakich, & Sharda, ).…”
mentioning
confidence: 99%
“…Selfe and Selfe (2008) added that creating podcasts, collages, video, blogs, audio essays, comic strips, and digital storytelling all fall under the types of MMC tasks. Smith (2017) suggested that MMCs often involve a huge number of visuals, sounds, movement, and written text to build synergistic messages. MMCs theoretically include many dimensions like social interaction, computer interaction, physical coordination, visual design, multiple language, musical accompaniment, and animation (Dallacqua, 2018).…”
Section: Focus On Readers and Discourse Communities Social Constructmentioning
confidence: 99%